Pengaruh Hedonic Shooping Motivations Dan Shooping Lifestyle Terhadap Keputusan Pembelian Dengan Peran Self -Congruity Sebagai Mediasi Di Simple Store - Destria Issela Rhosa; Mohamad Rifqy Roosdhani (Universitas Dharmawangsa, 2026)
This study aims to determine the influence of Hedonic Shopping Motivations and Shopping Lifestyle on Purchase Decisions, with Self-Congruity as a mediating variable at Simple Store. This research employs a quantitative method using a questionnaire as the primary instrument. The population consists of all Simple Store consumers, the exact number of whom is unknown; therefore, an accidental sampling technique was applied. The minimum sample size was determined using the Hair formula, resulting in 100 respondents. Data were collected using a 5-point Likert scale and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4 software. The results indicate that hedonic shopping motivation and shopping lifestyle have a positive and significant effect on both purchase decisions and self-congruity. Furthermore, self-congruity significantly influences purchase decisions and serves as a mediating variable that strengthens the relationship between hedonic shopping motivations and shopping lifestyle toward purchase decisions. These findings confirm that self-congruity is a crucial psychological bridge that transforms consumers' emotional drives into actual purchasing actions at Simple Store